Modell av en synkronmaskin för PSCAD/EMTDC med magnetisk mättning i d-led och elektriskt gränssnitt för fältmatare - Jonsson, Magnus (My University, 2003)
This report describes a synchronous machine model with magnetic saturation in d-axis, neutral connection and electrical exciter interface for the transient simulator PSCAD/EMTDC. It has been designed and verified in comparison to the regular machine model in EMTDC. The performance of the model is very good when incorporating a linear as well as a saturated magnetising inductance. The dynamic deviation is only thousandths to ten thousandths per unit. By using a cubic interpolation of the saturation curve, the model gives a good representation of the saturation effect. The open source code implementation of the synchronous machine model gives the possibility to easily adapt the model to specific requirements. The derived model makes it possible to simulate a synchronous machine with its excitation systems, e.g. a brushless exciter with ac/ac thyristor connection and rotating rectifier. Also, effects of fault and grounding of stator winding starpoint can be simulated.
Keywords: Elkraftteknik; Electric power engineering